PENGUATAN KEDUDUKAN DAN PERAN KOMISI APARATUR SIPIL NEGARA DALAM MEWUJUDKAN REFORMASI BIROKRASI - Harahap, Nurmalita Ayuningtyas (Jurnal Panorama Hukum, 2016)
As a non-structural institution is independent and free from political interferencethenstrengthening the position and role of State Civil Apparatus Commission (KASN) is indispensable in realizingbureaucratic reform. The topic being examined includes how the position and role of ASN is currently in realizing the reform of the bureaucracy and what efforts should be made to strengthen the position and role in realizing KASN current bureaucratic reforms.This is a normative legal research, the approach used in this research is a conceptual approach.The results of the discussion concludes the position and rolehas been regulated bythe law number 5 on 2014 aboutÃ‚Â  the state civil apparatus, the establishment of KASN in the region, authority to set a national policy on employment development.